Prinsip Dasar dan Aspek Filosofis Konsumsi dalam Ekonomi Syariah - Ahmad Arifin (Qonun Iqtishad EL Madani Journal, 2024)
The aim of this research is to find out and analyze the Basic Principles and Philosophical Aspects of Consumption in Sharia Economics. This research is referred to as library research, namely research carried out using library materials or library literature as written sources. Data was collected using a review technique of relevant references and related to the problems to be studied, especially the basic principles and philosophical aspects of consumption in sharia economics. The collected data is presented using qualitative descriptive and deductive methods. It is called descriptive because the research describes the object of the problem based on facts systematically, carefully and in depth in the research study. In the data processing process, an interactive analysis mode is used through three channels, namely data reduction, data presentation, and drawing conclusions or verification. The collected data was analyzed using the deduction method. The results of this research are that the Islamic concept of Needs and Desires, which is something that is necessary for humans to function perfectly, is divided into dhruriyat (primary), hajiyat (secondary), and tahsiniyat (tertiary). The Concept of Utilities and Maslahah in Consumption. Utility in economics is the usefulness or satisfaction that consumers feel when consuming goods or services. Maslahah in Islamic economics refers to the benefits obtained from consumption in accordance with sharia principles. The differences between utility and maslahah include the objective nature of maslahah, its consistency with social problems, and the orientation towards goodness and welfare in Islamic economics. Consumerism and Consumption Balance in Islamic Economics. Consumerism is the urge to buy and own goods excessively without considering ethical values ​​or social impacts. The purpose of consumption in Islam is as a means of worshiping Allah and achieving falah, namely a noble and prosperous life in this world and the hereafter. Consumption based on the intention to gain Allah's approval, using halal goods, moderation, and paying attention to social balance can bring blessings to consumers and society